THE EFFECT OF FLASH CARD AND PICTURE STORY IN VOCABULARY TO THE SEVENTH GRADER - Hidayat, Khoirul; Habibi, Fajri (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractBased on the content standard, junior high school students are hoped to master vocabulary about 1000 words, and in this case, flash card with picture story is two of media that can be used to transfer vocabulary material for the students. The objective of this research is to find the significant differences of using flash card with picture story in vocabulary, and to find which medium is more effective to use as media in vocabulary. This research was true experiment design. Pre test and post test were use to collect the data. Study problems; (1) are there any significant differences between flash card with picture story in vocabulary mastery for the seventh grade students?, (2) which one is more effective media in vocabulary learning process, is it flash card or picture story?. As a source of data, the researcher utilized flash card with picture story to teach vocabulary for the students. The media help students to learn vocabulary easier and more interesting to understand the subject, so their vocabulary would increase. The result of the research, it was found the mean score of picture story in pre test is 53,86, in treatment is 81, and in post test 85,33. Meanwhile the mean score of the flash card media in pre test 59,33, in treatment is 73,5, and in post test is 80,66. It means that the studentâs vocabulary has increased, and significant difference of using picture story and flash card in vocabulary, and picture story was more effective to use.Â Keywords: Flash Card, Picture Story, Vocabulary